Facebook.com : global marketing opportunities and connectivity - Baack, Daniel W. (SAGE knowledge. Cases., 2016)
This case study investigates the unique marketing opportunities presented by the growing phenomenon of social media. Facebook has vastly increased opportunities to contact and connect with potential customers on an international basis, which causes a range of unique and traditional marketing challenges to arise.